Strengthening Community Economic Capacity in Sei Selincah through Gambier Jelly Candy Innovation - Ichsan, Onne Akbar Nur; Santoso, Budi; Pranata, Boby; Nurmaseli, Tri; Yanuriati, Anny; Hermanto, Hermanto (Penerbit Goodwood, 2026)
Purpose: This community service initiative was developed to strengthen local economic capacity and promote the utilization of indigenous natural resources within community-based enterprises. Research Methodology: The program specifically aimed to empower the residents of RT 01, Sei Selincah Subdistrict, Kalidoni District, Palembang City by introducing an innovative value-added herbal product in the form of gambir-based jelly candy. To achieve this objective, the service activities included program socialization, partner needs assessment, and technical training sessions that used simple kitchen equipment. Results: Participants were also trained in product packaging and labeling using basic branding tools like a label sticker paper, as well as in production cost calculation through spreadsheet software and simple marketing strategies using social media platforms. The pre-test and post-test results demonstrated a knowledge increase of 61.82%, with the average score rising from 62.67 in the pre-test to 94.85 in the post-test. Conclusions: The results demonstrated a notable increase in the participants’ technical skills, knowledge, and confidence, as evidenced by their ability to independently produce gambir jelly candies and initiate a small-scale home-based business. Limitations: Overall, the program effectively enhanced community competence, encouraged local product innovation, and supported long-term economic empowerment. Contributions: These outcomes contribute to sustainable livelihood development and strengthen the community’s self-reliance in creating functional herbal products with added value.